The Triggering Mechanism of Short Video Customer Inspiration – Qualitative Analysis Based on the Repertory Grid Technique - Gao, Peng; Jiang, Heng; Xie, Ying; Cheng, Yu (Frontiers in Psychology, 2021)
It is believed that stimulating short video consumers’ inspiration might be an effective way to attract and maintain consumers’ attention so that they are willing to respond positively to short video ads. Therefore, in order to explore the source of customer inspiration in short video and its’ cognitive psychological process, the text and grid data collected from an interview among 25 short video users have been qualitatively analyzed by Repertory Grid Technology so as to construct the formation path model of short video customer inspiration, and to find out it’s source, triggering mechanism, and influencing factors in a systematic way. It is found that the inspiring informational content characteristics include richness, reliability, vividness, and fluency; of emotional content characteristics, fun, novelty, and narrative. However, the characteristics of commercial content in short video ads hinder the inspiration of consumers. The study also reveals that an internal mechanism of inspiration stimulation is built on some cognitive processes (i.e. presence, processing fluency, perceived innovation, perceived convenience) that are generated by informational content, and emotional responses that are aroused by emotional content (i.e. curiosity, surprise, enjoyment, etc.). In addition, it is shown that personal involvement enhances the relationship between the inspiring content characteristics and consumer inspiration. As a result, customer inspiration and engagement in short video ads are highly enriched. Findings provide implications for short video platforms and online marketers.